2017
DOI: 10.1088/1755-1315/73/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distributed Generation on Overcurrent Relay Coordination and an Adaptive Protection Scheme

Abstract: Abstract. Integration of distributed generation (DG) such as renewable energy sources to electrical network becomes more prevalent in recent years. Grid connection of DG has effects on load flow directions, voltage profile, short circuit power and especially protection selectivity. Applying traditional overcurrent protection scheme is inconvenient when system reliability and sustainability are considered. If a fault happens in DG connected network, short circuit contribution of DG, creates additional branch el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The amount of fault current contributed by DER varies widely [32,34]. Generally, DER are connected with network via power converter, so the fault behaviour are depends on converter controller and its design parameter [35]. The contribution of Inverter Based Distributed Generation (IBDG) to the system's fault current level is the lowest [33].…”
Section: Fault Current Contributionmentioning
confidence: 99%
“…The amount of fault current contributed by DER varies widely [32,34]. Generally, DER are connected with network via power converter, so the fault behaviour are depends on converter controller and its design parameter [35]. The contribution of Inverter Based Distributed Generation (IBDG) to the system's fault current level is the lowest [33].…”
Section: Fault Current Contributionmentioning
confidence: 99%
“…In Ref. [19], typical value ranges are presented of the ratio between the output current and the short-circuit current:…”
Section: Impact Of Dg On Distribution Networkmentioning
confidence: 99%
“…An OC relay trip settings are determined by "pickup current (Ip)" and "time delay" parameters. Pickup current is the threshold current value and is sensed by current level detection principle, which has to be exceeded for relay trip [27].…”
Section: Settings Of Protective Devicesmentioning
confidence: 99%
“…The previous reports have focused more on the problems that are created by adding DG to the distribution networks, such as blind protection, sympathetic tripping and failure of reclosing [4,5,7,8]. In [10,12,22,[24][25][26][27], the recloser settings and coordination with the other protective devices such as fuses and overcurrent relays were studied. The researchers in one study [14] replaced a new solid dielectric with hydraulic reclosers and showed the benefits of this replacement.…”
Section: Introductionmentioning
confidence: 99%